A global knowledge, attitudes and practices survey on anatomical endoscopic enucleation of prostate for benign prostatic hyperplasia among urologists - TANIDIR, YILÖREN (WILEY, 2020)
There is an increasing use of the procedure, anatomical endoscopic enucleation of the prostate, as an alternative to conventional transurethral resection of prostate for surgical treatment of benign prostatic hyperplasia. However, barriers to adoption of this procedure remain and no prior studies explored this important aspect till date. The aim of this study is to identify the predictors and barriers of surgeon-related practices in this area. The study findings may also provide valuable insight into current practice trends worldwide. To achieve the objectives, we conducted an online, cross-sectional, questionnaire-based study between 1st September 2019 and 5th October 2019 to investigate the knowledge, attitudes and practices among urologists worldwide. Our findings showed that the main barriers for adoption of the procedure were lack of mentorship, a steep learning curve, and unavailability of morcellator, bipolar or laser energy sources. Fear of urinary incontinence, bleeding and bladder injury were not major hindrance to adoption of this technique. The results also demonstrated that there will be continued increase in utility of the procedure in the future.
Keywords: AEEP; benign prostatic hyperplasia; social media; urology; UroSoMe; HOLMIUM LASER ENUCLEATION; SURGICAL-MANAGEMENT; PRACTICE GUIDELINES; LEARNING-CURVE; RESECTION; HOLEP; AUA